Distinction by proxy: The democratization of fine wine. (June 2013) - Howland, Peter J.
In the 17th-century wine was transformed from a simple, bulk commodity to one distinguished by vineyard, vintage, grape varietals and the ephemerality of cellaring, and increasingly consumed in public theatres of consumption. This laid the foundations for the emergence of wine connoisseurship and a conspicuous link with elite social distinction. In the 1970s the New World wine industries democratized the cultural and social capitals of appreciative wine consumption, while retaining its capacity to stratify. Democratization enables connoisseurship by proxy and for middle-class individuals with variable wine tastes and aspirations to readily transform their economic capital into cultural capital and thus enact distinction-signifying performances. This is significant in Martinborough, a boutique wine village renowned for high-quality wines and an objectified, performative site of middle-class distinction. In consuming fine wines Martinborough's tourists are structurally validated in middle-class distinction, personalized tastes and reflexive individuality.